ANALISIS WEWENANG PEMERINTAH DALAM KUASA DISKRESI ADMINISTRASI - Rizki Syafril; Rika Efrina; Vionanda Aliza Putri; Yulvia Chrisdiana (Journal of Education on Social Science (JESS), 2023)
Analyzing how the government's authority is in the power of administrative discretion is the background for the author to discuss the study of administrative discretion, to determine the authority of an administrative agency or official to make decisions and take actions that are not prescribed by law or regulation, but are consistent with the goals and objectives of the agency or official. Because in essence, this discretion becomes an authority of government officials in issuing decisions or taking actions on their initiative. This study uses a method of data collection based on a literature review study. In using this method, researchers collect data by reading and processing several sources of books, articles, online media, and others as supporting material for their research. Planning carried out by the government and its authority is in line with discretion which is a form of action that has been planned by the authorized government to find a solution to problems that occur within the scope of its government based on statutory rules. Discretion needs to pay attention to procedures for use that can be accounted for morally and legally as regulated in the Act. There is a need for clearer and more effective rules to explain the abuse of authority in the anti-corruption law. Government policies will be categorized as deviant policies if they contain arbitrary elements. In addition, policies are considered deviant if they conflict with the public interest. Furthermore, the Government Administration Law states that the exercise of discretion must be exercised by senior government officials and citizens who have suffered losses due to the use of discretion, and this can be verified through law enforcement efforts or prosecution in the state administrative court